The Use of Social Media in Indonesian Language Learning for Students at Lamongan Islamic University - Emalia Nova Sustyorini; Etty Umamy (INFOKUM, 2026)
This study aims to describe the use of social media in Indonesian language learning for students at Lamongan Islamic University and examine students' responses to its use as a learning medium. The study used a descriptive qualitative approach with students from two classes of general Indonesian language courses as subjects. Data were obtained through learning observations, semi-structured interviews, student response questionnaires, and documentation of learning activities through social media. Data analysis was carried out through the stages of data reduction, data presentation, and continuous conclusion drawing. The results show that social media is used as a medium for communication and discussion, material delivery, and a means of practicing language skills, especially writing and speaking. The use of social media encourages increased academic interaction, active student participation, and learning motivation in Indonesian language learning. In addition, learning becomes more contextual and relevant to the characteristics of students as digital learners. The conclusion of this study shows that the integration of social media in Indonesian language learning contributes positively to the achievement of learning objectives and has the potential to be developed as part of an innovative learning model in higher education.